2017
DOI: 10.3390/cancers9060068
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Tumor Invasion by Tumor-Associated Macrophages: The Role of CSF-1-Activated Phosphatidylinositol 3 Kinase and Src Family Kinase Motility Signaling

Abstract: Macrophages interact with cells in every organ to facilitate tissue development, function and repair. However, the close interaction between macrophages and parenchymal cells can be subverted in disease, particularly cancer. Motility is an essential capacity for macrophages to be able to carry out their various roles. In cancers, the macrophage’s interstitial migratory ability is frequently co-opted by tumor cells to enable escape from the primary tumor and metastatic spread. Macrophage accumulation within and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 115 publications
(187 reference statements)
1
60
0
Order By: Relevance
“…Monocytes are recruited to the invasive front and differentiate into macrophages in response to signals from tumor and stromal cells. An array of cytokines (IL-4, IL-10, IL-13), chemokines (CCL2, CXCL12), and growth factors (CSF-1, TGF-β, VEFG-A, PDGF, angiopoietin-2) produced at the invasive margin stimulate monocyte recruitment, differentiation and survival ( 51 54 ). We have previously demonstrated that the chemokine receptor CCR6 is expressed on TAMs and facilitates their migration to the cancer site in a mouse model of mammary cancer.…”
Section: Cellular Mediators Of Cancer Cell Plasticity Via the Ecmmentioning
confidence: 99%
“…Monocytes are recruited to the invasive front and differentiate into macrophages in response to signals from tumor and stromal cells. An array of cytokines (IL-4, IL-10, IL-13), chemokines (CCL2, CXCL12), and growth factors (CSF-1, TGF-β, VEFG-A, PDGF, angiopoietin-2) produced at the invasive margin stimulate monocyte recruitment, differentiation and survival ( 51 54 ). We have previously demonstrated that the chemokine receptor CCR6 is expressed on TAMs and facilitates their migration to the cancer site in a mouse model of mammary cancer.…”
Section: Cellular Mediators Of Cancer Cell Plasticity Via the Ecmmentioning
confidence: 99%
“…In brief, macrophages secrete epidermal growth factor (EGF), which interacts with its target receptor (EGFR) on the surfaces of tumor cells [123]. This binding event activates EGFR signaling, thus, leading to the secretion of colony stimulating factor 1 (CSF-1), which in turn attracts macrophages via CSF-1 receptor (CSF-1R) [123,124]. This paracrine interaction between CSF-1-secreting tumor cells and EGF-secreting macrophages drives the migration of tumor cells and the macrophages toward blood vessels.…”
Section: Intercellular Connections Between Tumor Cells and Macrophagementioning
confidence: 99%
“…They may have an effect on the inactivation of T-cells, which crucially decreases the body's ability to resist cancer development and progression. 16 It has been shown that the patients with a large number of TAMs in cancer tissue have worse surgical outcome compared to the patients with a lower number of TAMs. TAMs also promote tumor angiogenesis, enhance metastatic spreading and contribute to invasion by producing cytokines such as IL-6, IL-17, IL-23 and inhibiting cytotoxic T lymphocyte responses.…”
Section: Macrophages and Cancermentioning
confidence: 99%